Emotional Engagement with VAK-Informed Multimodal EFL Materials among Indonesian Senior High School Learners - Rina Asrini Bakri; Saiful; Rahayu; Anugerah Febrian Syam (Darul Yasin Al Sys, 2026)
Students’ emotional engagement remains a persistent challenge in many English as a Foreign Language (EFL) classrooms, where instruction is frequently dominated by teacher-centered approaches and textbook-based materials. This study aimed to explore how multimodal EFL materials informed by Visual, Auditory, and Kinesthetic (VAK) learning principles shaped students’ emotional engagement in an Indonesian senior high school. A qualitative case study was conducted at SMA Negeri 20 Gowa during the 2024/2025 academic year. Through purposive sampling, one Grade XI class (XI-B) was selected from approximately 180 students based on its relatively comparable English proficiency and learning characteristics. Data were collected through classroom observations, semi-structured interviews, students’ reflective journals, and classroom documentation and analyzed using thematic analysis. The findings revealed five interconnected dimensions of emotional engagement: interest and enjoyment, confidence, motivation, active participation, and sense of belonging. Learning activities integrating visual, auditory, and kinesthetic experiences created a more interactive and supportive classroom environment, encouraging students to participate more confidently and collaboratively. Students also perceived the learning process as more enjoyable, meaningful, and relevant than conventional instruction. These findings demonstrate that VAK-informed multimodal materials can support emotionally engaging and learner-centered EFL instruction by strengthening students’ affective involvement, meaningful participation, and communicative interaction. This study contributes to the literature on emotional engagement and multimodal pedagogy by providing context-specific evidence from Indonesian secondary EFL education and offers practical implications for teachers designing inclusive instructional materials that accommodate diverse modes of learning.